Effects of a health literacy enhancement program on health promoting behaviors and hemoglobin A1C level among elderly with Type 2 Diabetes - Duangsanjun, Winut; Suttharattanakun, Sirilak; Kiriram, Praman (Thai Journal of Nursing, 2022)
This quasi-experimental research aimed to determine effects of a Health Literacy Enhancement Program on health promoting behaviors and hemoglobin A1C level among elderly with type 2 diabetes. A sample of 44 elderly with type 2 diabetes, was purposively selected. They were equally divided into the comparative and experimental group. The research instruments included Health Literacy Enhancement Program, a questionnaire on health promoting behavior, and hemoglobin analyzer. Data were analyzed using descriptive statistics, Mann-Whitney U test, Wilcoxon signed-ranks test, and t-test. The results revealed that after experiment, health promoting behaviors of the experimental group was significantly higher than before experiment and the comparative group (p < .05). Hemoglobin A1C level of the experimental group was significantly lower than before experiment and the comparative group (p < .05).